ANALISIS UNSUR-UNSUR INTRINSIK DALAM HIKAYAT CERITA TAIFAH - Sumasari, Yoani Julita (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2015)
The study is aimed at analyzing the intrinsic elements in an old prose titled â€œHikayat Cerita Taifahâ€ (The Legend of Taifah). The objective of the study is to reveal the intrinsic elements of the story in such a way that the prose can be read, enjoyed and beneficial for the present society. Theoritically, the benefit of the study is to give inputs to the learning of old Malay Literature at schools and to provide learning material regarding elements of literature work, particularly in prose genre. The practical benefits expected is to build the strong character and to develop good personality of the young generation. Keywords : analysis, intrinsic elements, legend, the story of Taifah.